CHARACTERISTICS OF THE NUSANTARA ISLAMIC EDUCATION MODEL - yahya, hafidh hafidh (TAWASUT, 2024)
AbstractLooking at history, Islamic education in the Nusantara cannot be dated in origin based on the process of spreading Islam in the Nusantara. Islamic education in the archipelago cannot be separated from the dynamics of the development of Islam in the Nusantara. Since Islam was present in the archipelago, Islamic education has actually shown its form although it is still very simple. Of course, there are shifts, changes, and discoveries in it which are still ongoing. What is examined in the writing above is an effort to bring together as well as formulate Islamic education in the archipelago using Islamic and archipelagic characters. By emphasizing the orientation and style of education, at least it can describe how the concept of Islamic education is in the frame of Islam Nusantara.Keywords: Nusantara Islamic Education, Characteristics, Orientation and Style of Education.